Predictive Validity of Developmental Screening Questionnaires for Identifying Children With Later Cognitive or Educational Difficulties: A Systematic Review - Schonhaut, Luisa; Maturana, Andres; Cepeda, Olenkha; Serón, Pamela (Frontiers in Pediatrics, 2021)
Context: Parent/caregiver completed developmental screening questionnaires (DSQ) for children before 5 years of age are currently recommended. The DSQs recommended by the American Academy of Pediatrics (AAP) are the Ages and Stages Questionnaires (ASQ), Parents' Evaluation of Developmental Status (PEDS) and the Survey of Well-being of Young Children (SWYC). Nevertheless, their predictive validity has not been well established. Objective: To assess in the current literature the value of AAP recommended DSQs (ASQ, PEDS, SWYC) administered between 0 and 5 years of age, for predicting long term cognitive achievement and/or school performance (CA/SP), after one year or more of evaluation and at/or after age 5 years, in general population. Data Sources: Cochrane, Medline Pubmed, CINAHL, Embase, Web of Science, Scielo and Scopus databases (until March 2021). Study Selection: Two authors selected the studies. Forward and backward citation follow up was done; authors of DSQ were contacted to identify additional studies. Data Extraction: Cohorts were identified, and authors of selected studies were contacted to corroborate and complete extracted data. Results: 32 publications, corresponding to 10 cohorts were included. All cohorts used ASQ. Only cohort using PEDS was identified but did not meet the inclusion criteria. No cohorts conducted with SWYC were identified. Associations between ASQ and CA/SP were extracted for 8 cohorts. The odds ratios were >3 and the area under the curve 0.66-0.87. A trade-off between sensitivity and specificity is observed. Limitations: Heterogeneity in population characteristics and in DSQ adaptations. Conclusions: A positive association between ASQ and later CA/SP was found in different social, cultural and economic settings. Additional studies are necessary to determine the impact factors in the predictive capacity of DSQs.